Allium ursinum L. на Лівобережному Поліссі України - Rak, A.A.; Lukash, A.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2007)
Spreading of Allium ursinum L. on the Left-Bank of the Dnieper river of Ukrainian Polissia was established. Ecological and coenotic peculiarities of the location, age and spatial structure of the population of this plant species have been studied. The reasons for rare occurrence of a species in the region are found.